Should Mother–Baby Rooming-In be the Standard of Care?. Issue 2 (March 2015) - Beal, Judy A.; Dalton, Marcia Fonseca; Maloney, Joyce A.
<x xml:space="preserve">Abstract</x> How strict should policies be for keeping new mothers and babies together while in the hospital during postpartum?